MENCIPTAKAN IKLIM KELAS YANG KONDUSIF MELALUI SISTEM PENGAJARAN BERBASIS DATA - Purwandari, Septiyati; Cholimah, Nur; Pradana, Agrissto Bintang Aji (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
Getting to know students became a crucial in teaching that teachers often did not consider about. This study aimed at collectinginformation related to early-elementary grade students experiencing a data-based learning. Then, teachers were expected to knowthe characteristics of their students as a reference to improve the quality of teaching and learning. The subjects of the study were50 students. They were all early-elementary grade students of MI Annur from first up to third grades. Data triangulationwas employed for assuring the validity. The technique of data analysis was qualitative descriptive explaining three components,including (1) awareness of learning; (2) awaereness of feelings; (3) and visionary thinking. The results revealed that on thefirst components most of the students prefered to play and learn as easy activities. They learned better when they were pleased.On the second components they were able to manage their socio-emotional condition seen from the answers related to their likesand dislikes, interests, and from their ability to express a happiness as the one they needed during their learning. On the thirdcomponents, the results revealed that most of them had goals achieved in learning. Besides, they were able to appropriately choosethe TV programs well-suited to their developmental levels. The results led us to have deeper understanding that knowing ourstudents really matters for building a conducive classroom climate.